Do regional government green innovation preferences promote industrial structure upgradation in China? Econometric assessment based on the environmental regulation threshold effect model - Khattak, Shoukat Iqbal; Khan, Aarif Mohammad; Khan, Muhammad Kamran; Li, Chen; Liu, Jiating; Pi, Zhuojie (Frontiers in Environmental Science, 2022)
China has been upgrading the industrial structure (ISU) at the regional level through innovation to achieve socioeconomic progress, but there is less known about the complex intermediary mechanisms regulating the government’s green innovation preference (GGIP)-ISU nexus from a regional perspective in China. Experts agree that varying environmental regulations (ER) intensity alters the relationship dynamics between innovation and ISU. Thus, using regional panel data (2005–2019), the paper develops an ER-based threshold regression model to assess the GGIP-ISU nexus under various ER levels in China. Following the statistically acceptable stationarity test outcomes, the regression corroborated the GGIP had disrupted ISU in China. Second, the ER-threshold model depicted that GGIP flexibility and ER rigidity were found interconnected, while the GGIP-ISU connection was characterized by a U-shaped relationship in which ER acted as a threshold variable. Third, the region-based heterogeneity test reflected that there was significant disparity in the inhibitory effect of GGIP on ISU between resource and non-resource-based regions, i.e., GGIP had a more significant inhibitory influence on the ISU in the non-resource-based regions than in the resource-based regions. The paper recommends critical policy implications for the enhancement of ISU in China.